CGIAR System Internal Audit Function Quality Assurance and Improvements Program - CGIAR System Organization (CGIAR System Organization, 2018)
Purpose: This document outlines a Quality Assurance and Improvements Program (QAIP) which is designed to provide reasonable assurance that the CGIAR System Internal Audit Function: Performs its work in accordance with its Terms of References, the Charter and is consistent with the International Professional Practice Framework (IPPF) of the Institute of Internal Auditing (IIA); operates in an effective and efficient manner, and; meets stakeholder expectations as to be adding value and continuously improving.